Evaluasi Proses Bisnis Menggunakan Metode Quality Evaluation Framework (QEF) (Studi Kasus: Bali Kencana Bakery) - Wira Kumara; Aditya Rachmadi; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Bali Kencana Bakery is a manufacturing company specifically in bread production, the products that are produced include bread often found in a canteen, mini markets, and a few supermarkets in Denpasar city. As a manufacturing company, the main process of this company is production, other than production, there are many other supporting processes such as procurement of raw materials, receiving orders and complaints, packaging, and so forth. However, in reality, not all of the processes go as planned, there are a few problems that can cause financial loss, working overtime, and other problems that can hinder the company from achieving the target. Indications of problems generally occur in the business functions of production and packaging. Based on the problems mentioned, this study is done to determine the root cause of the problem. Starting from mapping out the main business function and supported by using Value Chain Analysis (VCA). Further, the business function that needs to be evaluated will be modeled into a business process through Business Process Modelling Notation (BPMN). This study uses Quality Evaluation Framework (QEF) to evaluate after finding the discrepant Quality Factor, a Root Cause Analysis (RCA) will be used to determine the root cause of the Factor. The results from using the RCA will help the company in administering changes to reduce loss and working hours. There are five (5) quality factor codes that have been found to be problematic from this study and the category of manpower and machine as the most contributor to the occured problems.